The training and development process for a world-class female handball player: a longitudinal and retrospective case study - Haugen, Thomas; Bucher Sandbakk, Silvana; Sandbakk, Øyvind; Tønnessen, Espen (Frontiers in Sports and Active Living, 2025)
IntroductionLimited information is available regarding the development of young talents who successfully follow the pathway to professional handball. The aim of this study was to retrospectively investigate the longitudinal training and development process of a world-class female handball player.MethodsAn intrinsic case study design was used to capture the quantitative and qualitative aspects related to the training and development process. We used a three-step data collection process and pragmatic analyses of (1) training logs/plans and performance statistics, (2) in-depth semi-structured interviews with three of the player's coaches, and her mother, and (3) systematic quality assurance through interviews to clarify, expand and validate preliminary findings with all informants followed by negotiation among researchers and all key informants, including the player.ResultsThe player's exceptional performance level was achieved by a gradual increase in training volume from ∼50 to ∼300 h·y−¹ between the ages of 7 and 15, then nearly doubled and plateaued at ∼600 h·y−¹ for the remaining career, with handball-specific training and physical conditioning accounting for 300–350 and 250–300 h·y−1, respectively. Practically all training was organized, and training in other sports was conducted up to the age of 14. Approximately 80%–90% of the physical conditioning consisted of strength training, while the remaining 10%–20% consisted of endurance training. Key training and development features included early engagement in handball combined with cross-over sampling of various sports during childhood and youth, early introduction and consistent implementation of physical conditioning throughout the career, participation in well-coordinated talent development initiatives, early exposure to adult-level practice and competition, and low injury rate. Key athlete characteristics included a multidimensional sports talent, discipline, dedication, a development-oriented mindset, a strong ability to handle setbacks, and an empathetic nature. Environmental success factors encompassed a sport-enthusiastic family, high-quality training environments, and access to domain-specific expertise.DiscussionThis study provides novel information regarding the training and development process for a female world-class handball player. The findings may provide a framework for how future talents, as well as their coaches, family, training peers, and national sports federations, can effectively coordinate efforts to enhance long-term athletic development and performance outcomes.